Effect of a Multistarter Yeast Inoculum on Ethanol Reduction and Population Dynamics in Wine Fermentation - Zhu, Xiaolin (Foods, 2021)
Microbiological strategies are currently being considered as methods for reducing the ethanol content of wine. Fermentations started with a multistarter of three non-Saccharomyces yeasts (Metschnikowia pulcherrima (Mp), Torulaspora delbrueckii (Td) and Zygosaccharomyces bailii (Zb)) at different inoculum concentrations. S. cerevisiae (Sc) was inoculated into fermentations at 0 h (coinoculation), 48 h or 72 h (sequential fermentations). The microbial populations were analyzed by a culture-dependent approach (Wallerstein Laboratory Nutrient (WLN) culture medium) and a culture-independent method (PMA-qPCR). The results showed that among these three non-Saccharomyces yeasts, Td became the dominant non-Saccharomyces yeast in all fermentations, and Mp was the minority yeast. Sc was able to grow in all fermentations where it was involved, being the dominant yeast at the end of fermentation. We obtained a significant ethanol reduction of 0.48 to 0.77% (v/v) in sequential fermentations, with increased concentrations of lactic and acetic acids. The highest reduction was achieved when the inoculum concentration of non-Saccharomyces yeast was 10 times higher (10(7) cells/mL) than that of S. cerevisiae. However, this reduction was lower than that obtained when these strains were used as single non-Saccharomyces species in the starter, indicating that interactions between them affected their performance. Therefore, more combinations of yeast species should be tested to achieve greater ethanol reductions.